Psychometric Evaluation of the Chinese Version of the Decision Regret Scale - Richard Huan Xu; Ling Ming Zhou; Eliza Laiyi Wong; Dong Wang; Jing Hui Chang (Frontiers in Psychology, 2020)
ObjectiveThe objective of this study was to evaluate the psychometric properties of the Chinese version of the decision regret scale (DRSc).MethodsThe data of 704 patients who completed the DRSc were used for the analyses. We evaluated the construct, convergent/discriminant, and known-group validity; internal consistency and test–retest reliability; and the item invariance of the DRSc. A receiver operating characteristic (ROC) curve was employed to confirm the optimal cutoff point of the scale.ResultsA confirmatory factor analysis (CFA) indicated that a one-factor model fits the data. The internal consistency (α = 0.74) and test–retest reliability [intraclass correlation coefficient (ICC) = 0.71] of the DRSc were acceptable. The DRSc demonstrated unidimensionality and invariance for use across the sexes. It was confirmed that an optimal cutoff point of 25 could discriminate between patients with high and low decisional regret during clinical practice.ConclusionThe DRSc is a parsimonious instrument that can be used to measure the uncertainty inherent in medical decisions. It can be employed to provide knowledge, offer support, and elicit patient preferences in an attempt to promote shared decision-making.